New England BK consortium: Regional survey of BK screening and management protocols in comparison to published consensus guidelines. Issue 6 (19th September 2018) - Gabardi, Steven; Pavlakis, Martha; Tan, Chen; Francis, Jean; Cardarelli, Francesca; Asch, William; Bodziak, Kenneth; Chobanian, Michael; Gilligan, Hannah; Gohh, Reginald; Kung, Shiang‐Cheng; Inker, Lesley; et al.
Abstract: Introduction: BK polyomavirus (BKPyV) continues to impact renal transplant recipients (RTR). The New England BK Consortium aims to jointly optimize screening and management of BKPyV. Methods: Our first project was to survey centers' BKPyV screening protocols and compare them to consensus guidelines. Results: Thirteen of 15 centers (86.7%) returned the survey. Only two center reported using monitoring parameters that were in line with consensus guidelines for BKPyV screening, while the majority of centers reported less intensive methods and shorter duration. One center reported performing renal biopsies in all patients with plasma viral loads >10 000 copies/mL, while all other centers only perform for‐cause biopsies. For presumptive nephropathy, 11 centers recommend a biopsy for confirmation. For management of documented BKPyV‐associated nephropathy, 12 centers propose further immunosuppression reduction. Nine centers report CNI dose reduction as their primary treatment. More than half of centers surveyed reported use of leflunomide, cidofovir or intravenous immunoglobulin. Conclusions: There was a large variance in BKPyV screening and management strategies among centers. Due to these results, all participating centers agreed to implement uniform screening and aim to optimize management protocols.